2018
DOI: 10.3847/2041-8213/aab889
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR Detection of X-Ray Heating Events in the Quiet Sun

Abstract: The explanation of the coronal heating problem potentially lies in the existence of nanoflares, numerous small-scale heating events occuring across the whole solar disk. In this paper, we present the first imaging spectroscopy X-ray observations of three quiet Sun flares during the NuSTAR solar campaigns on 2016 July 26 and 2017 March 21, concurrent with SDO/AIA observations. Two of the three events showed time lags of a few minutes between peak X-ray and extreme ultraviolet (EUV) emissions. Isothermal fits wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…NuSTAR observations have allowed multiple detailed studies of sub-A-class events in active regions, as well as one paper concerned with three even smaller (GOES∼A0.01) quiet Sun brightenings (Glesener et al 2017;Wright et al 2017;Kuhar et al 2018;Cooper et al 2020). The spectra of events in Glesener et al (2017), Kuhar et al (2018), and Cooper et al (2020) were best fit by isothermal spectral models throughout their evolution, though the Glesener et al (2017) microflare displayed some high-energy excess over this fit during the impulsive phase. Preflare, postflare, and decay-phase spectra of the event presented in Wright et al (2017) were also best fit by a single thermal model, but the addition of a second higher-temperature thermal model was required to account for high-energy excess during its impulsive phase.…”
Section: Nustar Solar Observationmentioning
confidence: 99%
“…NuSTAR observations have allowed multiple detailed studies of sub-A-class events in active regions, as well as one paper concerned with three even smaller (GOES∼A0.01) quiet Sun brightenings (Glesener et al 2017;Wright et al 2017;Kuhar et al 2018;Cooper et al 2020). The spectra of events in Glesener et al (2017), Kuhar et al (2018), and Cooper et al (2020) were best fit by isothermal spectral models throughout their evolution, though the Glesener et al (2017) microflare displayed some high-energy excess over this fit during the impulsive phase. Preflare, postflare, and decay-phase spectra of the event presented in Wright et al (2017) were also best fit by a single thermal model, but the addition of a second higher-temperature thermal model was required to account for high-energy excess during its impulsive phase.…”
Section: Nustar Solar Observationmentioning
confidence: 99%
“…This particular NuSTAR solar pointing 1 had spent 3 hours focused on active regions on the opposite western limb as they rotated off the visible disk, occulting the brighter emission from the lower solar atmosphere. NuSTAR briefly pointed at disk centre, during which it observed a small quiet Sun event reported in Kuhar et al (2018), before targeting the eastern region for 10 minutes. It then returned to the west limb for another hour.…”
Section: Observation Overviewmentioning
confidence: 99%
“…Since the first solar NuSTAR observations in 2014 (see Grefenstette et al 2016;Hannah et al 2016;Kuhar et al 2017), solar activity has decreased allowing sub-A class microflares to be observed regularly within ARs (Glesener et al 2017(Glesener et al , 2020Wright et al 2017;Hannah et al 2019) and small brightenings outside of ARs (Kuhar et al 2018). 8 The AR microflares observed by NuSTAR have been found to have thermal energy releases down to 10 27 erg with quiet Sun brightenings having energies down to 10 26 erg.…”
Section: Introductionmentioning
confidence: 99%